Peran Wisata Batu Alam Mahpar dalam Edukasi Sejarah di Tasikmalaya (2017-2024) - Hariri Jabal Syukur; Moch Azka Shohibul Musyaffa; Luqman Nurhakim (Badan Penerbit STIEPARI Press, 2025)
This study aims to describe the history and role of Batu Alam Mahpar Tourism as a space for local historical education in Tasikmalaya during the 2017–2024 period. The research employs a descriptive qualitative method with a historical approach, encompassing heuristics, source criticism, interpretation, and historiography. The findings reveal that Batu Alam Mahpar underwent development in three main phases: local exploration and branding (2017–2019), pandemic adaptation (2019–2021), and educational consolidation (2022–2024). Batu Alam Mahpar educational role is reflected in the presentation of historical narratives through community museums and oral history. Despite challenges such as limited human resources and digitalization, Batu Alam Mahpar continues to serve as a relevant model of place-based education rooted in community participation. This research highlights the importance of institutional support and the integration of local historical education within the context of community engagement-based tourism.